Development of EV charging templates: an improved K‐prototypes method. Issue 20 (31st May 2018) - Hong, Juhua; Xiang, Yue; Liu, Youbo; Liu, Junyong; Li, Ran; Li, Furong; Gou, Jing
Abstract : In order to manage the charging behaviour of electric vehicles (EVs), this study for the first time develops a set of EV charging load profiles: EV templates. EV charging profiles have unique waveforms similar to a rectangular pulse train. This characteristics significantly limits the performance of clustering analysis in that traditional distance calculation, such as Euclidean distance, which cannot reflect the morphological dissimilarities. This study proposes a novel clustering method using rough set theory to accurately measure the dissimilarity between the EV profiles. The pulse train waves are firstly extracted as mixed data features, which are partitioned by an improved K‐prototypes method based on rough set distance. The proposed method is implemented on the real charging load profiles and compared with K‐means and traditional K‐prototypes. Their clustering performances are evaluated by diverse validity indices. The results show that the proposed method outperforms other comparison methods.